Selebritisme dan Inferiority Complex Syndrome - Mastur, Mastur (AL-TAZKIAH, 2013)
Human is anorganism that always tends to have a pleasure. He calls it as the Id mechanism (a biological aspect of human being) which always demands an actualization of its satiation. Indonesian society on sociology perspective is as a society which was colonized by capitalism countries, even up to present it is still under the grip of capitalism countries (well known as neo-imprialism). This phenomenon grows and increases the hedonistic culture and consumptive culture toward Indonesian society. Celebritisme phenomenon (pop culture/Hollywood culture) toward Indonesian society, its teenagers, becomes a proven of individual and social reality (two assumptions mentioned previously). Mass media, then, has a great role in influencing personal counsciousness and it directs Indonesian society to be have what mass media exposes or present. Mass media contextually, has adominant and great role in growing and developing celebritism mentality of Indonesian society.